Colonial Encounters and Culinary Fusion:: The Evolution of Indian Food Through Trade, Empire, and Globalization - Sailesh, Bhaskar; Karthikeyan K (Journal of Gastro Tourism, 2025)
An exploration of the culinary legacy left by colonialism in India to demonstrate how they met and negotiated with each other to create what is now modern Indian gastronomy. Those were its pre-colonial roots in Indian cooking, the defining part of which developed under the decisive influence of the Portuguese, British, French, and Dutch colonial powers, introducing new ingredients and techniques along with an entirely new manner of consumption. Through thematic sections: ingredient exchange, hybridized cuisines, and socio-political implications of these, the chapter makes an argument that the culinary fusions in India are not just a gastronomical outcome, but a narrative of adaptation, resistance, and identity building. Much of the contemporary matters now under consideration, including cultural appropriation, culinary diplomacy, and the balance between authenticity and innovation in a globalizing food economy. This chapter argues that India's culinary terrain is a living archive of colonial encounters and calls for a critical yet celebratory mode of reckoning with food heritage in post-colonial contexts. Keywords Adaptation, Anglo-Indian cuisine, Authenticity, Colonialism, Cultural identity, Culinary fusion, Diaspora, Fine dining, Globalization, Heritage, Hybrid cuisine, Indian cuisine, Innovation, Memory, Migration, Modernity, Postcolonial, Resistance, Soft power, Street food